Ischiospinal Dysostosis in a Child with Pierre-Robin Syndrome - Mahmoud Almasri; Waleed Kishta; Fahad H. Abduljabbar; Vincent Arlet; Neil Saran; Jean Oullet (Case Reports in Orthopedics)
Ischiospinal Dysostosis (ISD) is a complex and very rare medical entity. It is associated with kyphoscoliosis, dysplasia or aplasia of the ischial rami, segmental anomalies of the bony vertebrae, and peculiar facial morphologies. In this case report, we present a child with Ischiospinal Dysostosis and Pierre-Robin Syndrome. This case report is unique as we followed the patient for 13 years in which he had multiple spinal procedures to treat his kyphoscoliosis. In this paper, we elucidated the number of case reports with documented follow-up regarding spinal cord injury or other complications of ISD and its management.